Criterion Equations of Heat Transfer for „N“ Horizontal Pipes One above Another at Natural Convection in Linear Method of Approximation - Andrej Kapjor; Jozef Huzvar; Branislav Ftorek; Martin Vantuch (Communications - Scientific letters of the University of Zilina, 2014)
The aim of the analysis of heat and fluxional pipe fields”n“ pipes one above another at natural convection is the creation of criterion equation on the basis of which the heat output of heat transfer from pipe oriented areas one above another with given spacing could be quantified. For creating criteria-relation and calculating the Nusselt number for „n“ tubes one above the other were used computational data from Ansys-Fluent software and criterion equations for a single tube. Based on the heat transfer analysis of a single horizontal tube will be used criterial equation for calculating the Nusselt number according to Morgan. For themselves derive criteria equations data evaluated were calculated and adjusted for mathematical processing of results. Formation criterion equations was based on approximation of planar curves prepared from adjusted modeled data by using CFD. In calculating was used the least squares approximation method.